Epidemiological Factors Associated With Intraductal Papillary Mucinous Neoplasm of the Pancreas: A Dual Center Case-Control Study. Issue 3 (March 2022) - Bülow, Robin; Tjaden, Christine; Ittermann, Till; Hinz, Ulf; Klaiber, Ulla; Weiss, Frank-Ulrich; Aghdassi, Ali; Heckler, Max; Kromrey, Marie-Luise; Völzke, Henry; Hosten, Norbert; Büchler, Markus W.; et al.
Abstract : Objective: The present study aimed to identify epidemiological factors associated with the development of intraductal papillary mucinous neoplasms (IPMN) of the pancreas comparing patients after IPMN resection with population-based controls. Methods: Preoperative data of 811 patients undergoing pancreatic resection for IPMN were matched in a 1:1 ratio with a random sample of volunteers from the Study of Health in Pomerania, which showed no pancreatic cyst greater than 2 mm in magnetic resonance cholangiopancreaticography. Results: A total of 811 controls with a mean age of 61.9 years (standard deviation, 8.4 years) were matched to cases with a mean age of 66.1 years (standard deviation, 9.3 years). A previous history of pancreatitis, endocrine pancreatic insufficiency was significantly more frequent in IPMN patients compared with controls ( P = 0.001). Moreover, adjusted data revealed that urogenital cancer ( P = 0.034), colorectal cancer ( P = 0.021), as well as first-degree family history of colorectal cancer ( P = 0.001) were significantly more frequent in IPMN patients. Conclusions: A history of urogenital and colorectal cancer often coincides with IPMN, which have an indication for surgery and are associated with preoperative episodes of pancreatitis and with endocrine insufficiency. Prospective studies are needed to investigate the role of these factors in IPMN development.